Protective role of methanol extract of Phyllanthus polyphyllus against N-nitrosodiethylamine-induced liver tumor in rat - Maideen, Naina Mohamed Pakkir; Velayutham, Ravichandiran; Manavalan, Gobinath (Bangladesh Journal of Pharmacology, 2011)
The protective role of methanol extract of Phyllanthus polyphyllus was evaluated in N-nitrosodiethylamine-induced experimental liver tumor in male Wistar albino rats. Administration of extract (200 and 400 mg/kg) effectively suppressed liver tumor as revealed by decrease in elevated levels of Phase I enzymes like cytochrome P450, cytochrome b5, NADPH-cytochrome P450 reductase and glycoproteins like hexose, hexoseamine and sialic acid. The extract produced an increase in phase II enzymes like UDP-glucuronyl transferase and glutathione-S-transferase levels when compared to liver tumor bearing animals. This study suggests that methanol extract of P. polyphyllus may extend its protective role by modulating the levels of glycoproteins and phase I metabolizing enzymes and augmenting phase II metabolizing enzymes.